If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -4 + -6 = 12 + -10x Combine like terms: -4 + -6 = -10 -10 = 12 + -10x Solving -10 = 12 + -10x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '10x' to each side of the equation. -10 + 10x = 12 + -10x + 10x Combine like terms: -10x + 10x = 0 -10 + 10x = 12 + 0 -10 + 10x = 12 Add '10' to each side of the equation. -10 + 10 + 10x = 12 + 10 Combine like terms: -10 + 10 = 0 0 + 10x = 12 + 10 10x = 12 + 10 Combine like terms: 12 + 10 = 22 10x = 22 Divide each side by '10'. x = 2.2 Simplifying x = 2.2
| -99=-3(-7x-2) | | 6x+4x=200 | | -6.5+x=12.25 | | 6g-6-3-6g= | | -3y-12=5y+44 | | 12(n+7)=4(21+3n) | | y=3x^2(x^2) | | [4x-20]+5=12 | | 7x-(2+4x)= | | .3x-.06x=1.25 | | 4p+4q=40 | | -280=7(-5x-5) | | 271-5x=40x+21 | | 5n-4(5n-5)=50 | | 4(2x-7)=8-x | | 2=-(5x-7) | | 252=6(5x+7) | | 5a-(4)=21 | | 7(y+8)=9y+56 | | 5x+36=14x-45 | | 32=-81(1-5x) | | 5a-4=21 | | [2y+1]=-7 | | 3(4r-6)=78 | | [x+2]=7 | | -3(-m-2)=-18 | | x-14=-5-29 | | 25x+5(x-5)+10(x-9)= | | 4x+26=13x-82 | | 7(-b+2+7-1)=13+3b+5b | | 15b-9=51 | | X(x^2+3)=6+x^3 |